Le revenant dans l’œuvre de Toni Morrison : ou le corps hanté de la mémoire - Vanessa Sylvanise (Conserveries Mémorielles)
Toni Morrison’s work is dark and strong. Unearthing afro-am ericain community’s pains, inherited from history, her work contains this famous “Inquiétante étrangeté” symptomatic of the “fantastic” literary’s genre. Authentic incursions in the tormented memory of a “minority”, which has not done its mourning, each novels appears like a sort of exorcism-therapy, without which it can’t be possible living present or considering future. That’s why, we’ll study “Revenances and hantises” phenomenons, dark and frightening, in this particular work. Especially in Beloved, the most famous of her novels, in wich, throughout the ghost figure came back to hunting her mother, appears one of the hardest reality of human history : slavery experience. By fear and distress, one disguised way to build memory and root out old past ghosts, because more than living ones, chained up to their secrets, ghosts have so much things to say, that their simple apparition can shout. When memory is stopped, and bodies mutilated are threatened by annihilation, ghost character give flesh and body to memory, a body maybe hunted but determined to, to not let itself sink in “oblivion”.